The Dispute Resolution of Violation of Indonesian Forest Area Based on the Decision of The Supreme Court Number 269 K / TUN / 2018 - Aris Irawan (Syntax Corporation Indonesia, 2021)
This research aimed at analyzing the characteristics of resolution of forest area disputes based on the Decision of the Supreme Court Number 269K / TUN / 2018. This research used normative legal method with legal, case, and conceptual approaches. The results showed that the Decidendi Ratio of the Supreme Court’s Decision was inappropriate. It is because in the context of the principle of legal certainty, that the object of the dispute is not included in the PTUN Decree, because of the Decree of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 1 / Pbt / KEM-ATR / BPN / 2016, is an integral part of the execution of criminal law against the act of falsifying documents carried out by officials within the North Kalimantan National Land Agency (formerly East Kalimantan), in issuing the PT Nunukan Jaya Lestari HGU certificate. The Supreme Court’s consideration regarding the overlapping area between PT Adindo Hutani Lestari and PT Nunukan Jaya Lestari, covering ±3,500 Ha is also incorrect because it must be understood that the area claimed to be overlapping is a dispute of the forest area.